Influence of Mg on the structural and optical properties of LiNbO3 thin films grown by polymeric precursor method - Simões, A. Z. [UNESP]; Bouquet, V.; Moura, F. [UNESP]; Ries, A. [UNESP]; Zaghete, M. A. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications Ltd, 2005)
A polymeric precursor solution was used to deposit pure and Mg doped LiNbO3 thin films on sapphire substrates by spin-coating. The effects of magnesium addition on crystallinity, morphology and optical properties of the annealed films were investigated. X-ray diffraction patterns indicate the oriented growth of the films. Phi-scan diffraction evidenced the epitaxial growth with two in-plane variants. AFM studies show that the films are very homogeneous, dense and present smooth surfaces. The refractive index and optical losses obtained by the prism coupling method were influenced by the magnesium addition.
Keywords: LiNbO3; Thin films; Waveguides; Phi-scan diffraction; Polymeric precursor method; Sapphire substrates; X-ray diffraction patterns; Lithium alloys; Polymer films; Spin coating; X ray diffraction; Film growth